2022
DOI: 10.1177/00336882221112166
|View full text |Cite
|
Sign up to set email alerts
|

Perusall Encourages Critical Engagement with Reading Texts

Abstract: Perusall, a collaborative reading tool, was introduced in an advanced reading and writing skills course in Hong Kong to increase engagement with texts and encourage critical discussion during the COVID-19 face-to-face class suspension. Students were asked to use the Perusall platform to complete pre-class readings, highlight and annotate text and critically discuss and answer questions. In this innovation in practice article, we describe why we adopted Perusall and the pedagogical implications of doing so. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…During periods of ERT, some students may live alone with very little social interaction. Class activities-such as collaborative peer review sessions, synchronous work time on Google Docs, or websites such as Perusall (Kohnke and Har, 2022)can serve as an opportunity to facilitate students' social needs while also improving their learning experience. This recommendation also addresses students' expressed concern about receiving less writing feedback from their peers and instructor during the ERT period.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…During periods of ERT, some students may live alone with very little social interaction. Class activities-such as collaborative peer review sessions, synchronous work time on Google Docs, or websites such as Perusall (Kohnke and Har, 2022)can serve as an opportunity to facilitate students' social needs while also improving their learning experience. This recommendation also addresses students' expressed concern about receiving less writing feedback from their peers and instructor during the ERT period.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…It would be pedagogically enriching if more attention were given to investigating students’ language gains in teacher education and language courses to examine how Perusall and other similar COAPs could promote literacy and reading skills development. Kohnke and Har's (2022) study reported that students’ critical reading skills were enhanced, but seeing more examples of this would be helpful. Adams and Wilson's (2020) research was on pre- and in-service teachers’ engagement with the readings instead of literacy skills, which was the course the teachers were attending.…”
Section: Reflection and Future Pedagogical Directionsmentioning
confidence: 99%
“…Summing up the article by viewing this pedagogic innovation from a research perspective, I stress the following observation. Although there has been an increasing number of studies on the impact of Perusall on language-related learning, most of them centre around these areas: student engagement (Suhre et al, 2019), reading motivation (Li and Li, 2023), collaborative reading, reading skills development in general and critical thinking specifically in students in middle school (Issa et al, 2021) and in higher education (Cecchinato and Foschi, 2020; Fazza, 2021; Kohnke and Har, 2022; Lee and Yeong, 2018; Miller et al, 2018; Woodward and Neunaber, 2020). It would be pedagogically enriching if more attention were given to investigating students’ language gains in teacher education and language courses to examine how Perusall and other similar COAPs could promote literacy and reading skills development.…”
Section: Reflection and Future Pedagogical Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ikastaroan, irakasleak hainbat tresna aukera ditzake ikaskideekin, beste erakunde batzuetako solaskideekin edo solaskide ezezagunekin idatzizko edo ahozko interakzioa sustatzeko, besteak beste: wikiak , bideokonferentziak (Jauregi et al 2012), mundu birtualak -hala nola Second Life- (Kruk, 2022), sare sozialak -esaterako Facebook- (Akbari, Pilot eta Simons, 2015), mezularitza-zerbitzuak -WhatsApp, kasurako- (Alamer eta Al Khateeb, 2023) eta irakurketa sozializatuko aplikazioak -hala nola Perusall- (Kohnke eta Har, 2022). Halaber, lantaldeak edo coworking birtualeko espazioak erabiltzea bultza daiteke, hala nola Focusmate, banaka egin beharreko edo aspergarriak izan daitezkeen atazak egiteko.…”
Section: Lotura Sozialaren Zentzua Sustatzeaunclassified